Human Herpesvirus-6 in Relapsing Remitting Multiple Sclerosis - Ansam W (Journal of Global Pharma Technology, 2016)
Background: Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system. HHV-6 has been implicated in the pathology of relapsing Remitting MS. Objective: Study the relation between HHV-6 viremia and relapsing remitting MS. Methods: A case-control study conducted on MS patients. fifty blood samples were collected from relapsing-remitting MS patients-thirty samples from the patients at the time of remission and twenty samples from the patients at the time of relapse and fifty blood samples from apparently healthy controls. Viral DNA extracted from plasma samples, and then, HHV-6 DNA detected and measured by quantitative real-time PCR. Anti HHV-6 IgG and IgM antibodies measured by ELISA. Results: HHV-6 was detected in 22% (11/50) of MS patients, in 45% (9/20) of relapsing patients and 6.77% (2/30) in remission, while none of the controls was positive for the virus, (P=0.0013) (OR=11.45, P=0.045) (RR=2.9, P= 0.0003). IgG was positive in 48% (24/50) of MS patients and 56% (28/50) of the controls, (P=0.42). While IgM was positive in only 4% (2/50) of MS patients in the relapsing group, (P=0.49).Conclusion: HHV-6 could have a role in the pathology of relapses in MS patients and high viral load might be an indicator of relapse.Keywords: Relapsing-remitting MS, HHV-6, Real time PCR, IgG, IgM.